An approach to axillary swellings cytomorphological (fine needle aspiration cytology) study - Gopika, A; Shilpa, N; Kusumanjali, B (Asian Journal of Medical Sciences, 2022)
Background: The axilla, a triangular area which is located between the upper arm and thorax, contains blood vessels, nerves, lymph nodes, and fat. Axillary swellings can arise from these various mesenchymal tissues present in the axillary area. The most common palpable axillary masses are usually lymph nodes. Fine needle aspiration cytology (FNAC) is the first line investigative technique with differential diagnosis includes reactive hyperplasia, inflammatory conditions, granulomatous disorders and malignancy. FNAC is a rapid, less invasive, less traumatic, and easily accessible and a cheap diagnostic tool to differentiate the benign or the malignant nature of the swelling. Aims and Objectives: Study is undertaken to document the spectrum of axillary lesions. Value of FNAC as a rapid diagnostic tool in diagnosing the axillary lesions. Materials and Methods: Present study is an 18 months cross-sectional study carried out in department of pathology, tertiary care hospital. Patients demographic and clinical data were collected from request forms. Slides were reviewed and analyzed. Data were entered in microsoft excel and analyzed. Results: Out of total 110 cases analyzed, ratio of female to male is 3.07. There were 41.8% benign and 13.6% malignant cases. 42.7% were inflammatory and 1.9% congenital lesions (ectopic breast). The most common lesions encountered are from lymph node (51.8%) (lymphadenitis-most common) followed by soft tissue tumor (Lipoma – most common). Rare lesions include nonhodgkin lymphoma, hodgkin lymphoma, neurofibroma, and chondroid syringoma. Conclusion: FNAC is an outpatient-based accurate, rapid procedure helps in timely diagnosis of various axillary lesions including clinically and radiologically ambiguous cases. It also helps to discriminate benign and malignant lesions with less chances of false negative results.